CULTURAL HERITAGE OF KYRGYZSTAN THROUGH THE PRISM OF ABYLABEK ASANKANOV’S RESEARCH (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Abylabek Asankanov’s research plays a key role in the study of the cultural heritage of Kyrgyzstan, revealing the deep processes of national identity formation and the preservation of traditions in the context of social and historical changes. His works deal with the issues of transformation of Kyrgyz culture under the influence of modernization, urbanization and political changes, starting from the Soviet period and up to the present. Special attention is paid to the mechanism of transmission of cultural values between generations, the role of historical memory and the significance of the epic “Manas” in national identity. Exploring the interaction of Kyrgyz culture with neighboring nations and the impact of globalization, Asankanov shows how traditions adapt to new conditions while maintaining their uniqueness. His works provide an opportunity to better understand the processes that took place in Kyrgyz society and to comprehend the importance of cultural heritage in shaping the national spirit.
Keywords: Abylabek Asankanov, Cultural heritage, Kyrgyzstan, national identity, traditions, epic “Manas”, modernization, historical memory, socio-cultural development